Pemanfaatan Mading Kreatif Berbasis Gambar untuk Meningkatan Pemerolehan Kosa Kata 3 Bahasa Siswa di SD Negeri Made Jombang - Hidayat, Rohmat; Nashoih, Afif Kholisun; Fathurozi, Anang; Firmansyah, Erwin; Ariswanto, Muhamad; Mariska, Devi Dwi; Arina, Setia Dwi; Maysaroh, Maysaroh (Lembaga Penelitian dan Pengabdian Masyarakat UNWAHA, 2024)
Education has an important role in shaping the next generation of the nation, and one important factor is the use of learning media. Learning media such as wall magazines (mading) can help students understand lesson material more effectively. This community service program aims to: 1. increase interest in reading, 2. know, understand and increase vocabulary in Indonesian, English and Arabic. 3. increase students' motivation in the learning process so that they are more enthusiastic in learning. The target audience is 58 students from SDN Made consisting of 33 grade 5 students and 25 grade 6 students. This activity will be held on August 13, 2024. The method used in implementing this community service activity is Learning-Service, a teaching approach that emphasizes practical aspects that refer to the concept of applying lecture knowledge in the midst of society or communities and becoming a solution to problems faced by society, communities, and community institutions. The three stages carried out in implementing this program are preparation, implementation and evaluation. The results obtained by partners after participating in this implementation activity are knowledge about wall magazine-based learning media and the acquisition of new vocabulary including Indonesian, Arabic and English. This application is expected to motivate and facilitate students in the learning process and create a more enjoyable learning atmosphere.